The Export Performance of Indonesian Dried Cassava in the World Market - Nico Adi Putra Hutabarat (Agricultural Socio-Economics Journal, 2017)
As an exporter of dried cassava, Indonesia ranks third worldwide; following Thailand and Vietnam. Indonesia was among the top four of dried cassava producers in the world; however, between year 2000 and 2015, by average only 0.63% of the total production was exported. Indonesia needs to improve the competitiveness performance. This study investigates the growth in exports of Indonesian Cassava in the World Market. The Constant Market Share (CMS) was used to measure the growth in exports of Indonesian Cassava. Based on result of Constant Market Share (CMS), Indonesia, Thailand, and Vietnam maintained their share in the world market during the Global Economic Crisis, because the growth rates of dried cassava import relative quickly during the crisis. The crisis make the import of other commodities are decreased during the crisis. But, it did not happen for dried cassava. The dried cassava export to the world survived during this crisis.